RE-AIM Evaluation of the Alcohol and Pregnancy Project: Educational Resources to Inform Health Professionals About Prenatal Alcohol Exposure and Fetal Alcohol Spectrum Disorder - Payne, J.; Frances, K.; Henley, N.; D'Antoine, Heather; Bartu, Anne; O'Leary, C.; Elliott, E.; Bower, C.; Geelhoed, E. (SAGE Publications, 2011)
The objective was to evaluate the Alcohol and Pregnancy Project that provided health professionals in Western Australia (WA) with educational resources to inform them about prevention of prenatal alcohol exposure and fetal alcohol spectrum disorder (FASD). The authors developed, produced, and distributed educational resources to 3,348 health professionals in WA. Six months later, they surveyed 1,483 of these health professionals. The authors used the RE-AIM framework (reach, effectiveness, adoption, implementation, and maintenance) to evaluate the project. The educational resources were effective in producing a 31% increase in the proportion of health professionals who routinely provided pregnant women with information about the consequences of drinking alcohol during pregnancy. One hundred percent of the settings adopted the project, it reached 96.3% of the target population, it was implemented as intended, and the resources were maintained (http://www.ichr.uwa.edu.au/alcoholandpregnancy). The educational resources for health professionals have potential to contribute to reducing prenatal alcohol exposure and FASD.